2014
DOI: 10.5603/fm.2014.0038
|View full text |Cite
|
Sign up to set email alerts
|

Determination of normal splenic volume in relation to age, gender and body habitus: a stereological study on computed tomography

Abstract: Background: The aim of this study is to assess and document the dimensions of the normal spleen measured on computed tomography (CT) images (Folia Morphol 2014; 73, 3: 331-338)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 25 publications
(71 reference statements)
2
22
2
Order By: Relevance
“…The mean of spleen width was 4.79 ± 0.998 cm which is less than from study conducted in Bangladesh, Nepal, Kashmir, North India and Nigeria (8,42,44,61,63,64) and greater than from study conducted in Sudan and Northern Ethiopia (29,33).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The mean of spleen width was 4.79 ± 0.998 cm which is less than from study conducted in Bangladesh, Nepal, Kashmir, North India and Nigeria (8,42,44,61,63,64) and greater than from study conducted in Sudan and Northern Ethiopia (29,33).…”
Section: Discussionmentioning
confidence: 55%
“…The sonography assessment of spleen dimensions provides essential inputs for clinicians in daily clinical practice for proper diagnosis of splenomegaly (32,44,(53)(54)(55). The result of this study gives reference values which helps radiologist for appropriate diagnosis of diseases associated to splenomegaly and splenic atrophy, for the surgeons to appropriately design surgical cases associated to spleen, for hematologist and immunologist for proper diagnosis of various gastrointestinal and hematological diseases and forensic studies (56)(57)(58)(59).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The difference in means on the logarithmic scale was the ratio of geometric means after transforming the data back to the original scale. Multivariate linear regression analysis included the potential confounders age, gender and BSA up to one year before or after CT. 24,25 We carried out backward linear regression analysis with a p value for removal of 0.1. P values of less than 0.05 were considered to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The normal size of the spleen is 198 ± 88 сm3 (20-90 years old volunteers) and it has a peak value at the age of 50-60 and is evaluated in the same work as 221 ± 95 сm3 [14]. Henderson J.M., et al reported the size of the spleen in healthy volunteers group was 219 ± 76 cm3 and varied 6-10% on different studies of the same person [15].…”
Section: динамическое изменение объема селезенки при актг-эктопированmentioning
confidence: 99%